2009
DOI: 10.2516/ogst/2009014
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity Impact on SAGD Process Performance in Mobile Heavy Oil Reservoirs

Abstract: Résumé -Impact des hétérogénéités sur la production d'huiles lourdes mobiles par SAGD -L'augmentation de la demande en pétrole et l'existence de réserves conséquentes en huiles lourdes et bitumes vont motiver, dans les prochaines décennies, un effort important pour développer les réservoirs non conventionnels. Dans ce cadre, la production par drainage gravitaire soutenu par une injection de vapeur (SAGD) est une technique très prometteuse pour extraire les huiles lourdes des réservoirs épais et de forte perméa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…They identified two flow regions: near wellbore regions where shale distribution strongly affects SAGD performance and an above well region where SAGD performance is only altered when a long and continuous shale barrier exists. Similar results were obtained by Shin and Choe (2009) and Le Ravalec et al (2009). These authors showed that even small shale barriers located between injector and producer can affect the SAGD performance, whereas only much larger barriers (above 50 m) located above injector affect the SAGD performance.…”
Section: Introductionsupporting
confidence: 85%
“…They identified two flow regions: near wellbore regions where shale distribution strongly affects SAGD performance and an above well region where SAGD performance is only altered when a long and continuous shale barrier exists. Similar results were obtained by Shin and Choe (2009) and Le Ravalec et al (2009). These authors showed that even small shale barriers located between injector and producer can affect the SAGD performance, whereas only much larger barriers (above 50 m) located above injector affect the SAGD performance.…”
Section: Introductionsupporting
confidence: 85%
“…From the experimental results above, for multi-thermal fluid injection technique, with the exception of the conventional thermal recovery mechanisms of steam injection (reducing oil viscosity; heat expansion; changing relative permeability; steam distillation etc.) (Butler, 1991;Liu et al, 2000;Ravalec et al, 2009), there still have the EOR mechanisms as follow.…”
Section: Further Discussionmentioning
confidence: 93%
“…pool above the producer (Sharma et al (2011)). The height of the liquid pool is proportional to the subcool, which is the temperature difference between the injected steam and the produced fluids (Le Ravalec et al (2009), Gates and Leskiw (2010), Gotawala et al (2012)). Therefore, a small subcool leads to a small liquid pool height and subsequent live steam production, while a large subcool leads to the liquid occupying most of the steam chamber, resulting in suboptimal steam chamber growth.…”
Section: Introductionmentioning
confidence: 99%